Resonance fluorescence of noisy systems - Rafał A Bogaczewicz; Paweł Machnikowski (New Journal of Physics, 2023)
Light scattering from resonantly or nearly resonantly excited systems, known as resonance fluorescence (RF), has been gaining importance as a versatile tool for investigating quantum states of matter and readout of quantum information, recently including also the inherently noisy solid state systems. In this work we develop a general theory of RF in the low excitation limit on systems in which the transition energy is subject to noise for two important classes of noise processes: white noise fluctuations that lead to phase diffusion and an arbitrary stationary Markovian noise process on a finite set of states. We apply the latter to the case of random telegraph noise (TN) and a sum of an arbitrary number of identical random TN contributions. We show that different classes of noise influence the RF spectrum in a characteristic way. Hence, the spectrum carries information on the characteristics of noise present in the physical system.